Audit committee independence, financial expertise and financial restatements: empirical evidence in Malaysia - Noorhanim, Mohamad Zainal (2016)
This study examines the effect of audit committee characteristics namely audit committee independence, accounting background of the chairman of audit committee and financial expertise of audit committee members on the financial restatements of the public listed companies in Malaysia. Many studies that investigated the relationship between audit committee characteristics and financial restatements were done in foreign countries. Therefore, this study contributes to the literature in this field of study in Malaysia. The theoretical foundation of this relationship was supported by agency theory. The main source of information for this study was obtained from the annual reports for the fiscal year 2014. By using the logistic regression analysis, the results show that there is negative relationship between the audit committee independence and financial restatements. However, with regards the results for the accounting background of the chairman of audit committee and the financial expertise of audit committee members show that the relationship are not statistically significant. In order to get better understanding of the relationship between audit committee characteristics and financial restatements, this study also has discussed the implications and suggestions for future research.